Formulation and quality evaluation of chicken meat balls - Rejikumar T P (Department of Poultry Science, College of Veterinary and Aniaml Sciences, 1991)
A study was undertaken to examine the feasibility of formulation of chicken meat balls from deboned minced meat of broilers and to evaluate its shelf-life.